Prostate Cancer: Epigenetic Alterations, Risk Factors, and Therapy - Mankgopo M. Kgatle; Asgar A. Kalla; Muhammed M. Islam; Mike Sathekge; Razia Moorad (Prostate Cancer)
Prostate cancer (PCa) is the most prevalent urological cancer that affects aging men in South Africa, and mechanisms underlying prostate tumorigenesis remain elusive. Research advancements in the field of PCa and epigenetics have allowed for the identification of specific alterations that occur beyond genetics but are still critically important in the pathogenesis of tumorigenesis. Anomalous epigenetic changes associated with PCa include histone modifications, DNA methylation, and noncoding miRNA. These mechanisms regulate and silence hundreds of target genes including some which are key components of cellular signalling pathways that, when perturbed, promote tumorigenesis. Elucidation of mechanisms underlying epigenetic alterations and the manner in which these mechanisms interact in regulating gene transcription in PCa are an unmet necessity that may lead to novel chemotherapeutic approaches. This will, therefore, aid in developing combination therapies that will target multiple epigenetic pathways, which can be used in conjunction with the current conventional PCa treatment.